In situ-formed adhesive hyaluronic acid hydrogel with prolonged amnion-derived conditioned medium release for diabetic wound repair. (15th January 2022) - Zhang, Yiqing; Zheng, Yongjun; Shu, Futing; Zhou, Renjie; Bao, Bingkun; Xiao, Shichu; Li, Kai; Lin, Qiuning; Zhu, Linyong; Xia, Zhaofan
Abstract: Hydrogels have long been used for encapsulating stem cell-derived conditioned mediums to achieve skin regeneration after wounding. However, inappropriate mechanical strength, low adhesion and low elasticity limit their clinical application. To address these challenges, we engineered a hyaluronic acid-based hydrogel grafted with methacrylic anhydride and N-(2-aminoethyl)-4-[4-(hydroxymethyl)-2-methoxy-5-nitrophenoxy]-butanamide (NB) groups to encapsulate a lyophilized amnion-derived conditioned medium (AM-CM). This hydrogel can photopolymerize in situ within 3 s by photo-initiated free-radical crosslinking between methacrylate moieties. Meanwhile, the formed o-nitrosobenzaldehyde groups by photo-irradiation could covalently bond with the amino groups of tissue surface, which allowed strong tissue adhesion. Furthermore, the hydrogel possessed excellent mechanical properties, high elasticity, favorable biocompatibility and prolonged AM-CM release. Our further vitro and in vivo studies showed that the hydrogel significantly accelerated diabetic wound healing by regulating macrophage polarization and promoting angiogenesis. The engineered hydrogel with AM-CM release has high potential to treat chronic wounds in clinics. Graphical abstract: Unlabelled Image Highlights: The hyaluronic acid-based hydrogel was in-situ photo-crosslinked within 3 s with a single, simple step. The hydrogel had good biocompatibility, high elasticity and strong tissue adhesion. The hydrogel extended AM-CM release and protected these peptides from degradation. The hydrogel accelerated diabetic wound healing by regulating macrophage polarization and promoting angiogenesis.